2020
DOI: 10.1136/bmjgast-2019-000361
|View full text |Cite
|
Sign up to set email alerts
|

Risk of colorectal cancer in a population-based study 20 years after diagnosis of ulcerative colitis: results from the IBSEN study

Abstract: ObjectiveThe association between ulcerative colitis (UC) and colorectal cancer (CRC) is widely accepted, although attenuated risk has been reported in recent years. Colonoscopic surveillance is recommended with intervals based on established clinical risk factors. Nevertheless, a significant number of patients develop interval cancers, indicating the need of improved individualised assessment. In the present study, we evaluated clinical risk factors associated with CRC during a prescheduled follow-up 20 years … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 37 publications
0
6
2
Order By: Relevance
“…The editorial writers also highlight our finding that the incidence of IBD‐associated CRC, adjusted for population changes, has remained static. This contrasts with studies from Nordic countries that have reported declining colorectal cancer incidence rates 3,4 . We suspect this reflects more limited electronic integration of primary and secondary care records in the UK, compared to Nordic countries.…”
contrasting
confidence: 63%
See 1 more Smart Citation
“…The editorial writers also highlight our finding that the incidence of IBD‐associated CRC, adjusted for population changes, has remained static. This contrasts with studies from Nordic countries that have reported declining colorectal cancer incidence rates 3,4 . We suspect this reflects more limited electronic integration of primary and secondary care records in the UK, compared to Nordic countries.…”
contrasting
confidence: 63%
“…This contrasts with studies from Nordic countries that have reported declining colorectal cancer incidence rates. 3,4 We suspect this reflects more limited electronic integration of primary and secondary care records in the UK, compared to Nordic countries.…”
Section: N V I T E D E D I T O R I a Lmentioning
confidence: 99%
“…The overall prevalence exceeds 0.3% in North America, Oceania, and most European countries[ 2 ]. Inflammatory bowel disease (IBD) is the third highest risk factor for colorectal cancer (CRC), and 18% of IBD-related CRC cases occur in patients with a history of less than 8 years[ 3 ]. Cross-sectional imaging under endoscopy may accurately reflect current inflammation of the intestines.…”
Section: Introductionmentioning
confidence: 99%
“…Based on our findings and those from another recent study that used primary care records to identify cases and thereby control for tertiary centre bias, the incidence of CRC in IBD appears to be static 14,22,23 . It is contrary, however, to data from specialist endoscopy centres and from prospective population studies from Nordic countries that have reported falling CRC incidence rates 24–27 . It is unclear why CRC rates have fallen in Denmark, Norway and Sweden but not the UK over a similar timeframe, since it is likely that all four countries have adopted similar treatment‐targets: including the maintenance of remission with medical therapies, appropriately timed surgeries and the use of colorectal surveillance programmes 23,28–30 .…”
Section: Discussionmentioning
confidence: 47%
“…14,22,23 It is contrary, however, to data from specialist endoscopy centres and from prospective population studies from Nordic countries that have reported falling CRC incidence rates. [24][25][26][27]…”
Section: Key Results and Interpretationmentioning
confidence: 99%